Characterization of Yellow Fever Suspected Cases and Confirmed Outbreaks in a Southwest State, Nigeria, 2021 - Itse Olaoye; Akinola Fatiregun; Adewale M. Adejugbagbe; Modupeola Dosumu; Ekun Opeyemi; Zubairu Mahmud; David Adeleke; Tsemaye Jacdonmi; Aladesawe Adesokeji; Famokun Gboyega; Abiona Samuel (Shiraz University of Medical Sciences, 2022)
Background: Yellow fever (YF) is an acute viral hemorrhagic fever caused by the yellow fever virus and transmitted by Aedes mosquito species. Despite the availability of a very effective vaccine, yellow fever virus (YFV) remains a public health threat across Africa. Enhanced disease surveillance, vector control, and high vaccination coverages are key to the prevention and control of YF. This paper aimed to describe yellow fever surveillance in Ondo state and the outbreak investigation activities conducted in the LGAs where outbreaks occurred in the year 2021.Methods: This is a retrospective cross-sectional study. We conducted an epidemiological investigation of yellow fever suspected and confirmed cases in Ondo State in Nigeria in 2021, using the YF case-based surveillance data. We described outbreak investigation and response activities carried out in affected LGAs, where the outbreaks were confirmed.Results: A total of 62 suspected YF cases were reported from January to December 2021, with no record of mortality. More than half (53%) of the cases were between the age of 15 to 29 years. About three-quarter of the reported cases (73%) had received the YF vaccine. The overall attack rate was 1.33 cases per 100,000 population. Only 3 out of the 62 reported cases were confirmed as yellow fever cases.Conclusion: The resurgence of yellow fever in the state puts the state at high-risk for yellow fever transmission. To reduce the immediate risks to the health of the population, specific activities should be tailored towards increasing awareness on yellow fever transmission, prevention, and control. These include activities on risk communication and community engagement, active surveillance, vector control, strengthening of routine immunization, as well as continued implementation of preventive mass vaccination campaigns.